Write It Right: A Little Blacklist of Literary Faults - Bierce, Ambrose, 1842-1914? (Salt Lake City, UT : Project Gutenberg, 2004)
"Write It Right: A Little Blacklist of Literary Faults" by Ambrose Bierce is a guidebook on writing and language usage authored in the early 20th century. This instructional work aims to enhance precision in writing, providing readers with a comprehensive analysis of common literary faults and misuses in the English language. Bierce, known for his wit and critical approach, focuses on how clarity and correctness in word choice can significantly improve the quality of writing. The book systematically lists various words and phrases that Bierce considers misused or inappropriate, providing explanations for each. For instance, he critiques the use of "admission" for "admittance" or "afraid" for "fear," emphasizing the importance of using words correctly to communicate effectively. Throughout the text, Bierce also reflects his personal taste and the common linguistic errors he encounters, illustrating how precise language reflects clear thinking. This blacklist serves as both a cautionary guide for writers and a humorous examination of the language's intricacies, helping readers to recognize and correct their own mistakes in writing. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Clare Boothby, Ben Harris and PG Distributed Proofreaders
Keywords: English language -- Errors of usage